STRATEGIA BEZPOŚREDNIEGO CELU INFLACYJNEGO W POLITYCE PIENIĘŻNEJ BANKÓW CENTRALNYCH - Przybylska-Kapuścińska, Wiesława (Wydział Prawa i Administracji UAM, 2006)
The paper presents the essence of direct inflation targeting strategy. It begins with its different definitions. Three kinds of inflation targeting strategy are characterised: the fully-fledged, eclectic and the lite one. In conclusion the advantages and disadvantages of the strategy are presented The inflation targeting strategy is used by central banks in more than 20 countries. Its realization needs making decisions of technical and organizational character in the designating the inflation target, choosing the inflation indicator and the ways of articulating the inflation target and its level. Central banks apply different solutions, depending on the monetary policy of the state.
DIRECT INFLATION TARGETING STRATEGY IN THE MONETARY POLICY OF CENTRAL BANKS